Pengendalian Kualitas Produksi Air Minum dalam Kemasan (AMDK) Menggunakan Diagram Kendali MCUSUM dan MEWMA - Sari, Kurnia Mahraini Kartika; Harsyiah, Lisa; Baskara, Zulhan Widya; Zulhan Widya Baskara (Program Studi Matematika, 2025)
Quality control in the water production process at PT. X is an essential activity to ensure the quality of packaged drinking water (AMDK) is fit for consumption. Therefore, the water quality of PT. X production must always be closely monitored. To guarantee the safety of drinking water, it must meet microbiological, radioactive, Physical, and chemical requirements according to the regulations stipulated in the Indonesian Ministry of Health Regulation Number 2 of 2023. Quality control is performed using MEWMA and MCUSUM control charts since these control charts can detect shifts in the process mean. The results of applying MCUSUM and MEWMA control charts indicate that the water production quality is statistically out of control. After monitoring, it was found that PH is the most influential variable causing out-of-control situations. An ARL test was conducted to obtain a control chart with the best performance, where a smaller ARL value indicates better sensitivity in detecting shifts in the process mean. The MCUSUM control chart outperforms the MEWMA control chart, with an ARL value of and parameters and , compared to ARL MEWMA of with weighting parameter and .